Intervensi Psikososial Untuk Menurunkan PTSD dan Meningkatkan Resiliensi Warga Penyintas Bencana Tanah Longsor di Banjarnegara - Choirul Anam; Mutingatu Sholichah; Sri Kushartati (State Islamic University (UIN) Ar-Raniry, 2018)
The landslide disaster in Jemblung, Sampang, Karangkobar, Banjarnegara, Central Java, caused massive losses, 95 dead and 13 others missing, many wounded and loss of agricultural land and property rights and infrastructure damage. Initial assessment showed that after 9 months of the disaster, most of the survivors who participated in the study still showed symptoms of PTSD and a low level of resilience. Based on these data, this research is aimed to decrease PTSD and increase resilience among disaster survivors through psychosocial intervention. The study design is action research, involving 25 survivors. Data obtained through PTSD scale and resilience scale, analyzed by Wilcoxon-sign test statistic. Interview and observation data were analyzed qualitatively. The results showed a significant decrease in the symptoms of PTSD Z = -1,994 (p = 0.046; p <0.05), but no significant increase found in resilience score Z = -0.890, (p = 0.373; p> 0.05 ). the results of qualitative analysis showed the survivors started showing the spirit to restart the routine of making a living by producing snacks but some of the survivors had not been involved because they were still afraid to face the risks of changing jobs from farmers, so they still need further assistance